cn38772
cn38772
05-04-2020
Mathematics
contestada
g(n) = 2n + 4
f(n) = 2n^2 - 4
Find g(n) - f(n)
Respuesta :
jimdyess
jimdyess
05-04-2020
Answer:
-2n^2+2n+8
Step-by-step explanation:
g=2n+4
f=2n^2-4
g-f = 2n+4 - (2n^2-4) = -2n^2+2n+8
Answer Link
VER TODAS LAS RESPUESTAS ( 41+ )
Otras preguntas
An equation is shown below: 9(3x – 2) = 1 Which of the following correctly shows the first two steps to solve this equation? Step 1: 27x – 2 = 1; Step 2: 27x =
When vibrational motion in an object increases, which is a true statement? A. Kinetic energy, temperature, and thermal energy increase. B. Kinetic energy, temp
please help me with this page maybe extra points given
Simplify. 5 – [–(–2)] A. –3 B. 3 C. –7 D. 7
How many solutions does the equation 6s – 3s – 9 = –2 + 3 have? Only one None Two Infinitely many
Which of these actions could constitute a breach of the Civil Rights Act? A. The human resources department rejected Fatima’s application because she did not ha
Which of the following models a geometric sequence. Select all that apply. 1) The amount of cell phone users increases by 33% every year. 2) Amount of cakes
12. He yelled at Cindy ____ it were all her fault. A - as though B - like C - because D - although
Cephalopods such as squid and octopi can communicate by changing skin colors and sometimes even skin patterns. this type of communication is an example of a a
Which equation is quadratic in form? 2(x + 5)2 + 8x + 5 + 6 = 0 x6 + 6x4 + 8 = 0 7x6 + 36x3 + 5 = 0 4x9 + 20x3 + 25 = 0